Mobilization Started Within 2 Hours After Abdominal Surgery Improves Peripheral and Arterial Oxygenation: A Single-Center Randomized Controlled Trial. Issue 5 (20th March 2021) - Svensson-Raskh, Anna; Schandl, Anna Regina; Ståhle, Agneta; Nygren-Bonnier, Malin; Fagevik Olsén, Monika
Abstract: Objective: The aim of this study was to investigate if mobilization out of bed, within 2 hours after abdominal surgery, improved participants' respiratory function and whether breathing exercises had an additional positive effect. Methods: Participants were 214 consecutively recruited patients who underwent elective open or robot-assisted laparoscopic gynecological, urological, or endocrinological abdominal surgery with an anesthetic duration of >2 hours. They were recruited to a randomized controlled trial. Immediately after surgery, patients were randomly assigned to 1 of 3 groups: mobilization (to sit in a chair) and standardized breathing exercises (n = 73), mobilization (to sit in a chair) only (n = 76), or control (n = 65). The interventions started within 2 hours after arrival at the postoperative recovery unit and continued for a maximum of 6 hours. The primary outcomes were differences in peripheral oxygen saturation (SpO2, as a percentage) and arterial oxygen pressure (PaO2, measured in kilopascals) between the groups. Secondary outcomes were arterial carbon dioxide pressure, spirometry, respiratory insufficiency, pneumonia, and length of stay. Results: Based on intention-to-treat analysis (n = 214), patients who received mobilization and breathing exercises had significantly improved SpO2 (mean difference [MD] = 2.5%; 95% CI = 0.4 to 4.6) and PaO2 (MD = 1.40 kPa; 95% CI = 0.64 to 2.17) compared with the controls. For mobilization only, there was an increase in PaO2 (MD = 0.97 kPa; 95% CI = 0.20 to 1.74) compared with the controls. In the per-protocol analysis (n = 201), there were significant improvements in SpO2 and PaO2 for both groups receiving mobilization compared with the controls. Secondary outcome measures did not differ between groups. Conclusion: Mobilization out of bed, with or without breathing exercises, within 2 hours after elective abdominal surgery improved SpO2 and PaO2 . Impact: The respiratory effect of mobilization (out of bed) immediately after surgery has not been thoroughly evaluated in the literature. This study shows that mobilization out of bed following elective abdominal surgery can improve SpO2 and PaO2 . Lay Summary: Mobilization within 2 hours after elective abdominal surgery, with or without breathing exercises, can improve patients' respiratory function.